Comparison of growth and development of oriental fruit fly, Bactrocera dorsalis Hendel (Diptera: Tephritidae) Reared on Sweet Potatoes (Ipomea batatas L.) and Wheat Germ Artificial Diet - M.Y., Nurul Fatihah; M., Salmah; M.S., Hailmi; B., Noor Afiza; Y., Nornasuha; N., Norhayati (2018)
An oriental fruit fly, Bactrocera dorsalis (Hendel) is a global and economically important pest of agricultural food crops. However, basic life history information on this pest, which is vital for designing more effective control methods, currently still needs serious attention, particularly through the good rearing insect diet. Thus, this study aimed to determine and compare the growth and development of B. dorsalis reared on sweet potatoes (Ipomea batatas L.) and wheat germ based artificial diets under laboratory conditions. Four types of diets used were; orange sweet potato (OSP), purple sweet potato (PSP), white sweet potato (PSP) and wheat germ (WG) as a standard diet. Results showed that among the diets tested, the WG based diet displayed a significant difference (P<0.05) in the growth and development of B.dorsalis due to the higher nutritional value contained in the diet. Nonetheless, B. dorsalis growth and development on sweet potatoes based diet, particularly on OSP diet, showed similar results as WG based diet. There was a significant difference between a number of pupae obtained where WG recorded the highest number of pupae (17.33±0.33) followed by OSP (9.00±0.577), PSP (9.00 ±0.33) and WSP (8.00 ± 0.577). However, no significant difference was shown among the OSP, PSP and WSP based diets particularly on the number of pupae, the percentage of pupae, adult survival and duration from egg to adult. As a conclusion, this study showed that sweet potatoes can be used as an alternative economic source of artificial diets for B. dorsalis mass-rearing program in laboratory.